A Review of Smoke Quitting Ring using AI - Vanshika Bali; Pooja Sehgal; Dr. Ratandeep Kaur (International Journal of Engineering and Management Research, 2024)
Smoking cessation continues to pose a significant public health challenge on a global scale, highlighting the need for innovative solutions to effectively support individuals in their journey to quit smoking. Traditional cessation programs often fall short in providing personalized support, resulting in high rates of relapse. To bridge this gap, we introduce the AI-Enabled Smart Quitting Ring, a wearable device that combines biometric authentication, smoke detection sensors, and personalized AI-driven interventions. This cutting-edge device offers real-time support and monitoring, utilizing machine learning algorithms to adapt interventions based on user behavior. The Smart Quitting Ring is designed to revolutionize smoking cessation efforts by delivering tailored support and boosting user motivation, ultimately leading to improved long-term quit rates and enhanced public health outcomes.